Important notice to all authors and readers of "Rozprawy Inżynierskie" quarterly - Redakcyjny, Komitet (Engineering Transactions, 1990)
The Editorial Committee has decided that, starting with No. 1, vol. 39 (i.e., from the beginning of 1991), all papers in the journal will be printed in English.The journal will appear under the title "Engineering Transactions" (with the subtitle "Rozprawy Inżynierskie"). We do hope that this decision will make the "Engineering Transactions" accessible to more readers and authors of "Engineering Transactions" and will consider ably promote interest in the materials published in the journal.Editorial Committee